2011
DOI: 10.1016/j.cogpsych.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Mental models of Boolean concepts

Abstract: a b s t r a c tNegation, conjunction, and disjunction are major building blocks in the formation of concepts. This article presents a new model-based theory of these Boolean components. It predicts that individuals simplify the models of instances of concepts. Evidence corroborates the theory and challenges alternative accounts, such as those based on minimal descriptions, algebraic complexity, or structural invariance. A computer program implementing the theory yields more accurate predictions than these riva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Although several authors have pointed out that rules can incorporate quantification and relations (Goodman et al, 2008;Goodwin & Johnson-Laird, 2011;Piantadosi, Goodman, & Tenenbaum, 2010), most of the rule-based models in the literature focus on rules formulated in propositional logic. The rule-plus-exception (RULEX) model proposes that humans learn concepts by constructing conjunctive rules and remembering exceptions to these rules .…”
Section: Rule-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several authors have pointed out that rules can incorporate quantification and relations (Goodman et al, 2008;Goodwin & Johnson-Laird, 2011;Piantadosi, Goodman, & Tenenbaum, 2010), most of the rule-based models in the literature focus on rules formulated in propositional logic. The rule-plus-exception (RULEX) model proposes that humans learn concepts by constructing conjunctive rules and remembering exceptions to these rules .…”
Section: Rule-based Approachesmentioning
confidence: 99%
“…The analyses most relevant to this article 10 KEMP are presented by Feldman (2006) and Goodwin and Johnson-Laird (2011), who both focus on Feldman's data set of 76 Boolean concepts. Feldman's algebraic complexity approach and the mental models approach both account well for the data, but the mental models approach achieves slightly higher quantitative fits.…”
Section: Rule-based Approachesmentioning
confidence: 99%
“…The standard conceptual learning task is to present individuals with REVERSE ENGINEERING 5 instances and noninstances of a concept, and their task is to learn to identify all and only the instances of the concept (e.g., Shepard, Hovland, & Jenkins, 1961). In a comparative study, Goodwin and Johnson-Laird (2011) showed that the difficulty of Boolean concept acquisition is likely to be dependent on the number of mental models underlying the concept. One of the model theory's predictions, which experimental results corroborate, is that it is easier to acquire a concept that is an exclusive disjunction*it has two models of its instances*than to acquire a concept that is an inclusive disjunction*it has three models of its instances.…”
Section: Boolean Circuitsmentioning
confidence: 99%
“…In particular, exclusive disjunctions are not always more difficult to deal with than inclusive disjunctions. In deductive reasoning, exclusive disjunctions are reliably easier than inclusive disjunctions (see, e.g., Bauer & Johnson-Laird, 1993); the same difference occurs in the acquisition of concepts (see, e.g., Goodwin & Johnson-Laird, 2011). The reason is that exclusive disjunctions are consistent with fewer possibilities than inclusive disjunctions.…”
Section: Reverse Engineering 21mentioning
confidence: 99%
See 1 more Smart Citation